Qualidade da carne de suínos submetidos a diferentes níveis de bagaço de oliva na dieta - Pereira, Denis do Couto (2023)
The production of extra virgin olive oil is growing in Brazil, especially in Rio Grande do Sul, generating large amounts of waste such as olive pomace (OP), which has a high contaminating power and, still, with little prospect of suitable destination. Considering the great availability and low cost of acquiring this residue, associated with its chemical composition rich in n-9 fatty acids and natural antioxidants, possibilities for its exploration to increase the quality of products of animal origin open up. In this context, the objective was to evaluate the effects of including OP in the pig growth-finishing diet on the quality of the meat produced. The field experiment was carried out at IFFar-SVS, while meat quality assessments were carried out at the Integrated Development Center for Laboratory Analysis (NIDAL) at UFSM. In the field experiment, 40 animals were used, distributed in a balanced way in four experimental treatments, consisting of diets based on corn and soybean meal with the inclusion of OP, preserved in the form of silage (OPS), at levels of zero (Control), 10, 20 and 30% on a dry basis. The animals were housed in pens with concrete floors, equipped with drinking fountains and feeders with an ad libitum feed supply, remaining there until slaughter, which occurred after 42 experimental days, with an average live weight of 90.6 kg ± 9.75 kg. After slaughter and cooling of the carcasses, the Longissimus thoracis (LT) muscle from the left half carcass of each experimental unit was removed, fractionated, identified and frozen (-20ºC) for subsequent laboratory evaluations. Evaluations of proximate composition, shear force, fatty acid profile and oxidative stability (TBARS and objective color) were carried out. The data obtained were subjected to statistical analysis, with a significance level of 5%. The results showed no effect (P>0.05) of the treatments on the proximate composition and shear force. However, the inclusion of OPS in the diets promoted a desirable change in the fatty acid profile, with an increase (P<0.05) in MUFA levels, mainly due to the increase in oleic fatty acid (C18:1n9), resulting in higher (P <0.05) unsaturated fatty acids content and reduction (P<0.05) of saturated acids. At the same time, the inclusion of 20% and 30% OPS levels resulted in lower TBARS values (P<0.05) during refrigerated storage (4ºC), indicating a favorable effect on maintaining lipid stability in the LT muscle.